yes or no???

Asked by  | 11th Apr, 2009, 11:10: AM

Expert Answer:

for the first equation,

substituting x=-1, y=1 gives,

LHS=2(-1) +3(1)=-2+3=1=RHS

Hence the (-1,1) satisfies the first equation.

Simly,

 we see that for the second equation,

substitution of x=-1 and y=1 does not satisy the equation 2. So it can't be the solution of the given system. Remember that a solution must satisfy  both the equations.

Answered by  | 11th Apr, 2009, 11:21: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.